PENGEMBANGAN ASESMEN PEMBELAJARAN RODA PUTAR TERINTEGRASI PROFIL PELAJAR PANCASILA MATERI SEJARAH KERAJAAN DI INDONESIA KELAS IV SD NEGERI KEDUNGKAMAL - Amanda Anggi Pramaishella; Arum Ratnaningsih; Titi Anjarini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to: First, develop an assessment product in the form of a spinning wheel learning assessment integrated with the Pancasila Student Profile for the topic of the history of kingdoms in Indonesia for fourth-grade students at SD Negeri Kedungkamal. Second, to determine the feasibility of the spinning wheel learning assessment integrated with the Pancasila Student Profile for the topic of the history of kingdoms in Indonesia for fourth-grade students at SD Negeri Kedungkamal. This research employs the R&D (Research and Development) approach using the ADDIE model, which consists of Analyze, Design, Development, Implementation, and Evaluation. The research subjects were 14 fourth-grade students of SD Negeri Kedungkamal in the 2024/2025 academic year. Data collection techniques included qualitative approaches (observation, interviews) and quantitative approaches (validation questionnaires from media experts, material experts, student responses, and teacher responses). Data analysis was conducted by measuring validity, practicality, and effectiveness. The research results are as follows: First, this study produced a product called the Spinning Wheel Learning Assessment Integrated with the Pancasila Student Profile for the topic of the history of kingdoms in Indonesia for fourth-grade students at SD Negeri Kedungkamal. Second, the product validity results showed a percentage of 91%, categorized as highly valid. The practicality results obtained a percentage of 99%, categorized as highly practical. The effectiveness aspect was evaluated based on student learning outcomes, where the limited trial achieved a score of 0.8 (high category), and the broader trial achieved a score of 0.69 (moderate category). Based on these findings, it can be concluded that the Spinning Wheel Learning Assessment Integrated with the Pancasila Student Profile for the topic of the history of kingdoms in Indonesia for fourth-grade students at SD Negeri Kedungkamal is feasible for use as a learning assessment in elementary schools.